Novel Diagnostic Methods in Ophthalmology - Nowinska, Anna (Biomedical Engineering, 2019)
In the last 10 years, there has been huge progress in the general understanding of ocular disorders due to the availability and development of new in vivo imaging techniques, such as anterior and posterior eye segment optical coherence tomography as well as biochemical methods allowing rapid confirmation of clinical diagnosis.Introducing noninvasive diagnostic methods in ophthalmology led to an improvement in early differential diagnosis of conditions such as corneal dystrophies, dry eye disease, and various retinal and optic nerve diseases.Recent advances in diagnostic methods have also impacted the treatment methods. This book intends to provide the reader with a comprehensive overview of current ocular diagnostic methods, including the theoretical basis as well as practical approaches and usage in clinical practice.